2017
DOI: 10.2131/jts.42.773
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the human relevance of the constitutive androstane receptor-mediated mode of action for rat hepatocellular tumor formation by the synthetic pyrethroid momfluorothrin

Abstract: -High dietary levels of the non-genotoxic synthetic pyrethroid momfluorothrin increased the incidence of hepatocellular tumors in male and female Wistar rats. Mechanistic studies have demonstrated that the mode of action (MOA) for momfluorothrin-induced hepatocellular tumors is constitutive androstane receptor (CAR)-mediated. In the present study, to evaluate the potential human carcinogenic risk of momfluorothrin, the effects of momfluorothrin (1-1,000 μM) and a major metabolite Z-CM-CA (5-1,000 μM) on hepato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 39 publications
4
38
0
Order By: Relevance
“…17 A number of investigative studies were performed to obtain data on the proposed key and associative events. [24][25][26][27] In some MOA studies, rats were also given sodium phenobarbital (NaPB), which is known to activate CAR in the rat and to produce a variety of hepatic effects including CYP2B enzyme induction and increased cell proliferation. 17 Phenobarbital (PB) (or NaPB) served as a positive control to confirm the potential responsiveness of the animals used in these MOA studies to a known CAR activator.…”
Section: Moa Analysis For Metofluthrin-and Momfluorothrin-induced Ratmentioning
confidence: 99%
See 2 more Smart Citations
“…17 A number of investigative studies were performed to obtain data on the proposed key and associative events. [24][25][26][27] In some MOA studies, rats were also given sodium phenobarbital (NaPB), which is known to activate CAR in the rat and to produce a variety of hepatic effects including CYP2B enzyme induction and increased cell proliferation. 17 Phenobarbital (PB) (or NaPB) served as a positive control to confirm the potential responsiveness of the animals used in these MOA studies to a known CAR activator.…”
Section: Moa Analysis For Metofluthrin-and Momfluorothrin-induced Ratmentioning
confidence: 99%
“…To evaluate the potential human carcinogenic risk of metofluthrin and momfluorothrin, the effects of these compounds on hepatocyte replicative DNA synthesis and CYP2B mRNA expression (an associative event, as a marker of CAR activation) were examined in cultured rat and human hepatocyte preparation. 26,27,40 The effect of PB was also investigated. 28 + indicates the effect is present at indicated time points of the treatment.…”
Section: Key Events Associative Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to study specific types of HCC, we need models that align well with various tumor subtypes. Additionally, some questions have been raised about whether CAR activation in humans causes direct DNA replication, and by extension, whether CAR is relevant to human HCC (50). Although the answers to these questions are still being investigated, our model shows a conserved gene signature with three independent sets of HBVrelated HCC.…”
Section: Discussionmentioning
confidence: 95%
“…74) Phenobarbital, a well-known liver tumor promoter in rodents, activates CAR in mice, rats, and humans, but induces DNA synthesis and hepatocyte proliferation only in rodents. For example, Yamada's group 75,76) demonstrated that hepatocyte growth factor increased DNA synthesis (BrdU labeling) in rat and human hepatocytes in vitro but phenobarbital did only in rat hepatocytes whereas it increased CYP2B6 and CYP2B1 mRNA levels in human and rat hepatocytes, respectively.…”
Section: Human Relevance Of Car-mediated Hepatocyte Proliferationmentioning
confidence: 99%